A Generalized Oblique Projection Filter with Flexible Parameter for Interference Suppression. (19th May 2015) - Wang, Yi-ming; Mao, Xing-peng; Hong, Hong; Zhang, Jie; Cui, Yu-mei
Abstract : A generalized oblique projection (GOP) with an adjustable parameter defined as interference suppression cost (ISC) is proposed. Therefore, an optional optimized signal to interference-plus-noise ratio (SINR) and user controlled actions on the interference filtering are presented in this GOP framework. Theoretical analysis and numerical simulation demonstrate that when the ISC is derived from minimum variance distortionless response (MVDR) algorithm, the SINR performance of GOP filter is better than both MVDR and oblique projection (OP) filters. Further, an application of GOP filter in ionospheric clutter cancellation in a high frequency surface wave radar (HFSWR) system is given. The ISC is designed specifically to introduce an extra coherent loss to the clutters and a satisfying clutter suppression result is achieved. Besides the examples given, more designs of GOP filter can be inspired by the flexibility of ISC. As a generalized form of OP filter, GOP filter expands the connotation of oblique projection based technique and could be used in spatial filtering, polarization filtering, and other array signal processing applications.